Optimization of the wavelength of lambda sensor - Hadi, Manap; Yasir, Hashim Naif; Alsibai, Alsibai; Muhammad Sharfi, Najib; Mohd Anwar, Zawawi
The increased importance of oxygen gas detection in many areas such as environment, clinical, food and automotive industries, promoted to a development of a new optical sensor. Most of the commercially available oxygen sensors are based on chemiabsorption sensors [1-3]. These types of sensors have their own drawbacks and have been discussed in previous report [4]. One of the main disadvantages is that they are not selective to a single gas alone especially when detecting the gas in the presence of other atmosphere gases [5]. Therefore a development of a new oxygen sensor using an optical method is necessary as an alternative method. In this research, the potential future development of an optical oxygen sensor in the UV region between 200-230 nm is reported.